Tinjauan Pustaka: Pengaruh Hipertensi Kronis pada Ibu Hamil terhadap Kejadian Preeklampsia - Putri, Morica Angellia Shyama; Kurniati, Intanri; Putri, Giska Tri; Kurniawati, Evi (CV. Jasa Sukses Abadi, 2025)
Chronic hypertension in pregnant women is a medical condition that can significantly affect maternal and fetal health. Chronic hypertension is defined as high blood pressure that has been present before pregnancy or diagnosed before 20 weeks of gestation. Risk factors that affect this condition include older maternal age, obesity, family history of hypertension, and an unhealthy lifestyle. The pathophysiology of chronic hypertension that progresses to preeclampsia involves endothelial dysfunction, which causes vasoconstriction and decreased placental perfusion, leading to placental hypoxia and increased oxidative stress, which further triggers activation of systemic inflammatory pathways causing damage to target organs such as the kidneys (proteinuria) and liver (elevated liver enzymes). The prevalence of chronic hypertension in pregnant women in Indonesia is quite high. According to data from the Lampung Provincial Health Office in 2018, hypertension in pregnancy caused 15.16% of maternal deaths. In addition, data from Riskesdas 2018 shows that the prevalence of hypertension in pregnant women in Indonesia is 6.18%, with the highest prevalence in West Java Province at 10.57%. The purpose of this article is to provide a better understanding of the effect of chronic hypertension in pregnant women on the incidence of preeclampsia. This article will discuss the association of chronic hypertension with the risk and underlying mechanisms of preeclampsia.